Getting the phase consistent: The importance of phase description in balanced steady‐state free precession MRI of multi‐compartment systems - Plähn, Nils M. J.; Poli, Simone; Peper, Eva S.; Açikgöz, Berk C.; Kreis, Roland; Ganter, Carl; Bastiaansen, Jessica A. M. (Magnetic resonance in medicine, 2024)
Purpose Determine the correct mathematical phase description for balanced steady‐state free precession (bSSFP) signals in multi‐compartment systems. Theory and Methods Based on published bSSFP signal models, different phase descriptions can be formulated: one predicting the presence and the other predicting the absence of destructive interference effects in multi‐compartment systems. Numerical simulations of bSSFP signals of water and acetone were performed to evaluate the predictions of these different phase descriptions. For experimental validation, bSSFP profiles were measured at 3T using phase‐cycled bSSFP acquisitions performed in a phantom containing mixtures of water and acetone, which replicates a system with two signal components. Localized single voxel MRS was performed at 7T to determine the relative chemical shift of the acetone‐water mixtures. Results Based on the choice of phase description, the simulated bSSFP profiles of water‐acetone mixtures varied significantly, either displaying or lacking destructive interference effects, as predicted theoretically. In phantom experiments, destructive interference was consistently observed in the measured bSSFP profiles of water‐acetone mixtures, supporting the theoretical description that predicts such interference effects. The connection between the choice of phase description and predicted observation enables unambiguous experimental identification of the correct phase description for multi‐compartment bSSFP profiles, which is consistent with the Bloch equations. Conclusion The study emphasizes that consistent phase descriptions are crucial for accurately describing multi‐compartment bSSFP signals, as incorrect phase descriptions result in erroneous predictions.